Ideology, Discourse, and Green Economy: A Comparative Analysis of Lazismu, Lazisnu, and Baznas in Indonesia - Kumara Adji; Sriyono Sriyono; Khairunnisa Abd Samad; Khoong Tai Wai (Perisai : Islamic Banking and Finance Journal, 2026)
This study examines how ideological paradigms shape the construction and implementation of green economy within Islamic philanthropic institutions in Indonesia. While existing studies on zakat predominantly focus on governance and socio-economic impact, little attention has been given to the ideological and discursive foundations underlying institutional practices. Addressing this gap, the study adopts a qualitative comparative approach to analyze three major zakat institutions—Lazismu, Lazisnu, and Baznas—which represent modernist, traditionalist, and state-driven paradigms, respectively.Drawing on a critical framework inspired by Michel Foucault, particularly the concepts of discourse and power–knowledge, this research demonstrates that green economy is not a neutral or universally defined concept, but a contested discourse shaped by institutional ideologies. The findings reveal that each institution articulates and operationalizes green economy differently: as a measurable sustainability framework aligned with global standards, as a culturally embedded expression of communal ethics, or as part of national development policy.The study contributes to the literature by advancing an epistemological perspective on zakat, highlighting the role of ideology in shaping economic-environmental practices, and proposing the possibility of a synthetic model of Islamic green economy. These findings offer both theoretical insights and practical implications for the development of sustainable Islamic philanthropy in diverse socio-religious contexts. Keywords: Islamic Philanthropy,  Zakat Institutions,  Green Economy, Discourse Analysis,  Ideology, Indonesia, Sustainability